Relationship Between Pregnancy Anemia and Depression in Postpartum Mothers: Systematic Review - Wijayanti, Poppy; Bainuan, Lina Darmayanti; Yuliana, Nur Aida (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2024)
Background: Anemia is one of the most significant global public health problems that affects a person's physical and mental abilities. Geography, lifestyle, and diet influence the prevalence of anemia in pregnant women, which is estimated to range from 14 to 80% in different countries (WHO, 2019. This study aims to analyze the relationship between pregnancy anemia and the incidence of depression in postpartum mothers. Subjects and Method: Systematic Review using the PRISMA diagram in the RevMan 5.3 application. Database searches from PubMed, Scopus, Wiley Online Library, and Science Direct were conducted in 2022-2024, and can be accessed for free, with the search terms